Performance Test of Residu Powder Distillation from Fermentation Result Cocoa Fruits (Theobroma Cacao L.) as Adsorbent For Metal Ions (Cr3+, Fe3+, Pb2+) - Kaharuddin Kaharuddin; Kurnia Sri Yunita; Muh. Edihar; Mawaddah Zaqinah Diah; Salniati Hade; Sapril Kartini (International Journal of Science Technology and Health, 2024)
Research this which is used as an adsorbent powder obtained through hydrolysis, fermentation and distillation of cacao fruit skin. This study aims to determine the ability of the cacao fruit skin powder to adsorb metal ions chromium (Cr3+), iron (Fe3+) and Lead (Pb2+) with adsorbent mass variation. Adsorption is done on metal chromium (Cr3+), iron (Fe3+) and lead (Pb2+) with three variations of the adsorbent mass of 0.25, 0.50 and 0.75 grams. The results showed that the performance of cacao fruit skin powder the most effective to metal ions lead (Pb2+) with percent adsorption 97.70%, for metal ions iron (Fe3+) with percent adsorption 94.33%, and crom (Cr3+) metal ions with the percent adsorption was 89.71% with adsorbent mass of 0.75 grams.